Dance anatomy - Haas, Jacqui Greene 1958- (Champaign, IL Human Kinetics, 2018)
Dance Anatomy is a visually stunning presentation of more than 100 of the most effective dance, movement, and performance exercises, each designed to promote correct alignment, improved placement, proper breathing, and prevention of common injuries.
The dancer in motion -- Brain health -- Injury prevention -- Spine -- Ribs and breath -- Core -- Shoulders and arms -- Pelvis and hips -- Legs -- Ankles and feet -- Whole-body training for dancers.
Includes bibliographical references.
Keywords: Dance -- Physiological aspects